2019
DOI: 10.1177/2167479518821913
|View full text |Cite
|
Sign up to set email alerts
|

Social Second Screen: WhatsApp and Watching the World Cup

Abstract: In recent years, changes have taken place in television viewing patterns during live broadcasts of major events. One of the most striking changes is the introduction of “second screens” that accompany viewing. The current study adds to the existing research literature by examining viewing patterns and socialization during the live broadcast of major sports games. Specifically, it examines the use of smartphones and WhatsApp among Israeli viewers of the 2018 World Cup games’ televised broadcasts, from the quart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 46 publications
3
20
0
Order By: Relevance
“…The study of Weimann-Saks et al (2020) also examined the Whatsapp use in Israel during the 2018 men’s FIFA World Cup. Based on an online questionnaire, the study focused on the effect that Whatsapp presence actually has on fans experience.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of Weimann-Saks et al (2020) also examined the Whatsapp use in Israel during the 2018 men’s FIFA World Cup. Based on an online questionnaire, the study focused on the effect that Whatsapp presence actually has on fans experience.…”
Section: Resultsmentioning
confidence: 99%
“…The popularity of the network in Israel, as mentioned, is particularly great and the shift of the discourse of the Whatsapp groups, which in the first place based on groups of friends who know each other outside the social network, to the sports sphere seems completely natural. Moreover, the study of Weimann-Saks et al (2020) even found connection between the viewer’s engagement with the game, Through the Whatsapp, and the enjoyment of watching the broadcast.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, while recent reports argue that 72% of adolescents report to media multitask with television and social network sites nowadays (GlobalWebIndex, 2019 ), this is not completely translated into the field of media multitasking research so far. While some studies started to show interest by investigating specific media multitasking behavior with social network sites (e.g., Beuckels et al, 2017 ; Weimann-Saks et al, 2020 ), this particular media multitasking behavior is not yet accounted for within all research topics until date.…”
Section: Research Gaps Within and Between The Different Topicsmentioning
confidence: 99%
“…Recently, researchers have investigated the relevance of social interactions within second screen usage during live sport events (Weimann-Saks et al, 2020). As previously mentioned, research topics were revived due to the disruptive potential of digitalization.…”
Section: Literature Review: Digital Transformation In Sport Managemenmentioning
confidence: 99%